This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can wrote n n + 1 = 1 + n 1 and n + 1 n + 2 = 1 + n + 1 1 , hence n n + 1 − n + 1 n + 2 = ( 1 + n 1 ) − ( 1 + n + 1 1 ) = n 1 − n + 1 1 Hence when we put sigma, it will be m → ∞ lim ( n = 1 ∑ m ( n 1 − n + 1 1 ) ) = m → ∞ lim ( 1 − m + 1 1 ) = 1
Indeed. Alternatively you can remove the 1 from every term as Kay did here. Ultimately, it's about accounting for lim m → ∞ T ( m ) .
Log in to reply
It is possible to do it without removing terms as well. If doing so, the limit evaluation will change to l i m m → ∞ n = 1 ∑ m ( 2 − n + 1 n + 2 ) = l i m m → ∞ ( 2 − m + 1 m + 2 ) = 2 − 1 = 1
[This is not a complete solution.]
Most people will think that this is an obvious infinite telescoping series, so all that we need to evaluate is T ( 1 ) = 1 1 + 1 = 2 .
But why isn't this the answer?
There will always be a non-zero term at the end which doesn't cancel.
To see how we shall consider the partial sum which telescopes:
n = 1 ∑ m ( n n + 1 − n + 1 n + 2 ) = 1 1 + 1 − m + 1 m + 2
Now let's take the limit as m tends to ∞ :
m → ∞ lim n = 1 ∑ m ( n n + 1 − n + 1 n + 2 ) = m → ∞ lim [ 1 1 + 1 − m + 1 m + 2 ] = 2 − 1 = 1
Log in to reply
Nice explanation. I nearly chose 2 as the answer until I rewrote the summand as 1 + n 1 − n + 1 ( n + 1 ) + 1 = n 1 − n + 1 1 , which does genuinely telescope.
Log in to reply
My sequence does genuinely telescope. It's just that the telescope is equal to T ( 1 ) − T ( n ) , and so when taking the limit to infinity, we actually get T ( 1 ) − lim n → ∞ T ( n ) . However, many people think that T ( ∞ ) = 0 , which need not be true.
Can you post this directly as a solution? Thanks!
Can we cancel infinity upon infinity
I fell for that. :(
The remained: \frac{1 + 1}{1} -~^\lim_{n \to \infty} \frac{n + 2}{n + 1} = 2 - 1 = 1
Alternative explanation: rewriting the series as the sum 2 = 1 2 + ( − 2 3 + 2 3 ) + ( − 3 4 + 3 4 ) + ⋯ is only valid if the series 1 2 − 2 3 + 2 3 − 3 4 + 3 4 − ⋯ is absolutely convergent; which of course it isn't (by e.g. the alternating series test) :)
Problem Loading...
Note Loading...
Set Loading...
n = 1 ∑ ∞ ( n n + 1 − n + 1 n + 2 ) = n = 1 ∑ ∞ n ( n + 1 ) n 2 + 2 n + 1 − n ( n + 1 ) n 2 + 2 n = n = 1 ∑ ∞ n ( n + 1 ) 1
Then decompose the fraction using n ( n + 1 ) 1 = n 1 − n + 1 1
n = 1 ∑ ∞ ( n n + 1 − n + 1 n + 2 ) = n = 1 ∑ ∞ ( n 1 − n + 1 1 )
= n → ∞ lim ( 1 1 − 2 1 + 2 1 − 3 1 + 3 1 − 4 1 + 4 1 + . . . − n 1 + n 1 − n + 1 1 )
= n → ∞ lim ( 1 − n + 1 1 ) = 1 .